The Jerusalem Oracle Reconsidered (Mt. 23.37–39): The Grammar of Messianism and the Future Coming of Jesus - Ferda, Tucker S. (Journal for the study of the New Testament, 2025)
An increasing number of exegetes have understood the Jerusalem oracle in Matthew and Luke to express a conditional eschatological perspective: namely, if ‘Jerusalem’ blesses Jesus along the lines of Ps. 118, then Jesus will return. Important for this argument has been the identification of similar conditional statements (so it is claimed) in later rabbinic sources. This essay argues against that interpretation, focusing on Matthew’s version, by uncovering an earlier and more widespread feature of ‘the grammar of messianism’: the use of temporal ‘until’ statements to refer to the coming of eschatological redeemer figures. Such messianic ‘grammar’ offers a more suitable parallel to Mt. 23.37–39 that is consistent with the eschatology of the rest of the Gospel, wherein Jesus’ future return is sudden, interrupts increasingly dismal circumstances, and brings about the hoped-for ingathering of God’s people.